ANALISIS PRODUK DOMESTIK BRUTO (PDB), SUKU BUNGA BI (BI RATE), DAN INFLASI TERHADAP INVESTASI ASING LANGSUNG (PMA) DI INDONESIA TAHUN 2006-2015 - Muhammad Akmal Fadilah; Tri Sukirno Putro; Anthony Mayes (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine the effect of the gross domestic product, the BI rate, and inflation on Foreign Direct Investment in Indonesia 2006-2015. The study consists of three independent variables (gross domestic product, the BI rate, and inflation) and one dependent variable (foreign direct investment). Foreign direct investment is the international flow of capital from a country where the company is establishing or expanding a company in another country. The data used are annual data from 2006-2015. The analytical method used is multiple linear regression using SPSS version 20.0. The research results obtained are GDP, BI rate, and inflation together (simultaneously) the effect on foreign direct investment with significance level of 5%. Partially BI rate has a negative effect on foreign direct investment, while the variable GDP and inflation partially positive effect on foreign direct investment. Variation factors that influence foreign direct investment is explained by GDP, the BI rate, and inflation together influential amounted to 98.0% (R2 = 0.98), while the remaining 2.0% is explained by other variables not included in this research. Between the three variables (GDP, BI rate, and inflation), the variable GDP and inflation have a significant effect on foreign direct investment.Keywords : Foreign Direct Investment, GDP, BI rate, Inflation